La influencia de la motivación en el desempeño laboral de los trabajadores agrícolas. - Zapata Constante, Francisco Xavier (2023)
Motivation is a key factor in the job performance of agricultural workers. The objective is to determine the influence of motivation on the work performance of agricultural workers of the company Procosecha de la Sierra S.A for the design of motivation strategies for the organization's personnel. The diagnosis proves that optimal working conditions do not exist in the company, there is low motivation and work performance is not adequate. An applied and descriptive research was carried out, with a qualitative-quantitative approach. The data collected showed that workers with high levels of motivation demonstrated better job performance compared to those with lower levels of motivation. Motivational factors identified included job satisfaction, sense of personal accomplishment, connection to the work community, and perception of fair rewards. The results of the research, through Pearson's Chi Square, reveal a statistically significant relationship between the motivation variables and work performance in the company Procosecha de la Sierra S.A in the city of Pujilí in the province of Cotopaxi. A Motivational Strategic Plan is designed that contributes to improving the motivation and work performance of workers. The proposal is evaluated by expert peer evaluators and users of the plan, recognizing the quality and relevance of the plan, highlighting its applicability and competitive advantages. The proposal provides a solid basis for its implementation in the company Procosecha de la Sierra S.A.